A comparison of web-based technologies to serve images from an Oracle9i database - Swales, Dylan (Rhodes University, Faculty of Science, Department of Computer Science, 2004)
The nature of Internet and Intranet Web applications has changed from a static content-distribution medium into an interactive, dynamic medium, often used to serve multimedia from back-end object-relational databases to Web-enabled clients. Consequently, developers need to make an informed technological choice for developing software that supports a Web-based application for distributing multimedia over networks. This decision is based on several factors. Among the factors are ease of programming, richness of features, scalability, and performance. The research focuses on these key factors when distributing images from an Oracle9i database using Java Servlets, JSP, ASP, and ASP.NET as the server-side development technologies. Prototype applications are developed and tested within each technology: one for single image serving and the other for multiple image serving. A matrix of recommendations is provided to distinguish which technology, or combination of technologies, provides the best performance and development platform for image serving within the studied envirorunent.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Active server pages; Microsoft .NET; JavaServer pages; Oracle (Computer file); Internet searching; Web site development--Computer programs; World Wide Web; Online information services